Application of the Scrum Method in the Android-based TPQ Learning Application - Willy Ramadani; T Sy Eiva Fatdha; Helda Yenni; Dwi Haryono (Universitas Islam Kuantan Singingi, 2023)
RA Alhikmah Kandis has the main material, namely learning TPQ (Al-Qur'an Education Park), learning to recognize, read, and memorize hijaiyah letters, daily prayers, and juz amma. With the development of technology, learning can now be supported by various innovations. One of the innovations is to create a mobile-based application for student learning at RA Alhikmah. The application is based on the design results based on the needs of students, teachers, and parents. Making applications using the Scrum method, applications that are built based on a predetermined time, where if the specified time has reached its end, then the application must be finished, is suitable for the Scrum method because its manufacture is based on a predetermined timeframe. Application testing uses the black box testing method to test whether each feature is running properly so that when used by application users, there are no bugs. This application is intended for raudhatul athfal or kindergarten children who are vulnerable aged 5 to 6 years, and this application can be accessed by accompanied by teachers when at school and parents when at home. The results obtained from the application black box testing can run well in all the features in the application. The author hopes that this application can provide the benefit of giving children a new method of learning to recognize hijaiyah letters, memorizing daily prayers, and juz amma in order to provide children's learning interest so that it is more interesting for their learning interest to get to know the Koran from an early age.